Post-emergence herbicidal activity of nanoatrazine against Alternanthera tenella Colla plants compared to other weed species - Sousa, Bruno Teixeira de; Pereira, Anderson do Espirito Santo [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Oliveira, Halley Caixeta; Dalazen, Giliardi (Elsevier, 2022)
The encapsulation of atrazine into poly(epsilon-caprolactone) nanocapsules has been shown to improve the efficiency of the herbicide and decrease its environmental impacts. In the current work, we evaluated the efficiency of nanoatrazine in the post-emergence control of Alternanthera tenella Colla plants and performed a meta-analysis to compare the results with studies already published with other weeds. The first experiment was carried out in the field, where we observed that nanoatrazine (at 200 g a. i. ha−1) induced higher inhibition of the maximum quantum efficiency of photosystem II (up to 39%) than conventional atrazine at the same concentration. However, nanoencapsulation did not improve the visually-determined weed control by atrazine. To better understand the response of A. tenella plants to nanoatrazine, a second experiment was carried out in a greenhouse with four-leaf stage plants treated with nano and conventional atrazine at 200, 500, 1000, and 2000 g a. i. ha−1. Nanoatrazine showed higher efficiency (up to 33%) than commercial atrazine in inhibiting photosystem II activity at all doses until 48 h after application. Again, weed control and plant dry mass did not differ between formulations. From the meta-analysis, it was observed that A. tenella plants showed a response to nanoatrazine that differs from other target species, as the gain in efficiency resulting from the nanoencapsulation was restricted to the short-term analysis, and did not result in better weed control. These results reinforce that the efficiency of nanoatrazine is dependent on the studied species.
Keywords: Atrazine; Calico plant; Meta-analysis; Nanoherbicides; Weed control